2020
DOI: 10.1088/1755-1315/437/1/012042
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of groundwater potential using the electrical resistivity method - Wenner Array

Abstract: Groundwater as a water resource has now become a complex national issue. Therefore, due to excessive groundwater abstraction, it is necessary to minimize the negative impact. This research aims to estimate groundwater level distribution and its possible use at the Faculty of Engineering of the University of Jember. A total path length of 392 meters was investigated. Field data was collected using a resistivity meter with the Wenner configuration method. In addition, the data obtained from the measurements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A rising demand for groundwater accompanies the increase in agricultural productivity. Investigative activities must be conducted through the surface or subsurface of the soil to discover aquifer layers, thickness, and depth [2] to explore groundwater's potential. Using groundwater without proper planning, management, monitoring, and protection can have consequences for the quality and quantity of IOP Publishing doi:10.1088/1755-1315/1311/1/012025 2 groundwater and the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…A rising demand for groundwater accompanies the increase in agricultural productivity. Investigative activities must be conducted through the surface or subsurface of the soil to discover aquifer layers, thickness, and depth [2] to explore groundwater's potential. Using groundwater without proper planning, management, monitoring, and protection can have consequences for the quality and quantity of IOP Publishing doi:10.1088/1755-1315/1311/1/012025 2 groundwater and the surrounding environment.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that sand as a primary aquifer has groundwater potential, encompassing 11.5% of the research area. The groundwater potential assessment was conducted in the Faculty of Engineering of the University of Jember, Indonesia, using the geoelectrical Wenner configuration method [9]. The result led to groundwater potential at the Faculty of Engineering of the University of Jember, classified as moderate productive, and distribution is located at a depth of 25.3-39.7 m, which indicated that the soil layer at this location contains plain alluvium deposits and coarse to medium grain gravel and sand, with the addition of clay.…”
Section: Introductionmentioning
confidence: 99%